Localized Supply Chain Solutions for Sustainable Community Development: A Strategic Model for Economic Revitalization and Regional Resilience - Uchechukwu Nkechinyere Anene,; Tosin Clement, (International Journal of Scientific Research in Science and Technology, 2024)
This paper presents a strategic model for localized supply chain solutions aimed at fostering sustainable community development, economic revitalization, and regional resilience. In the face of increasing global disruptions ranging from pandemics and geopolitical tensions to climate-related challenges communities require agile, localized frameworks to support equitable growth and sustainable development. The proposed model centers on decentralizing supply chains, enhancing regional self-reliance, and leveraging local resources, labor, and knowledge to reduce dependency on external systems. Drawing from systems thinking, circular economy principles, and place-based development strategies, this model integrates economic, social, and environmental dimensions to build robust local economies. It emphasizes value-added production within communities, shortened logistics chains, and the use of digital platforms to connect local producers, distributors, and consumers. Through strategic collaboration between public institutions, private enterprises, and civil society, the model encourages inclusive participation and shared ownership of regional development initiatives. A key component of the framework is the incorporation of sustainable procurement practices and green infrastructure to align with environmental goals, while supporting local entrepreneurship, workforce development, and innovation. By prioritizing local sourcing, manufacturing, and distribution, the model not only enhances economic resilience but also reduces carbon emissions, encourages circular material use, and strengthens community identity. The model also outlines policy recommendations and implementation pathways, including incentives for small and medium enterprises (SMEs), regional investment hubs, workforce training programs, and digital infrastructure for supply chain visibility and transparency. Case examples illustrate how localized supply chain initiatives have revitalized struggling rural economies and reinforced urban-rural linkages. This paper contributes to the discourse on sustainable development by demonstrating how restructured, community-centered supply chains can serve as engines for long-term economic stability, social equity, and environmental stewardship. It provides a practical roadmap for policymakers, planners, and stakeholders aiming to design adaptive and inclusive supply chain ecosystems that are resilient to future disruptions.
Keywords: Localized Supply Chains; Sustainable Development; Community Resilience; Economic Revitalization; Regional Self-Reliance; Circular Economy; Local Sourcing; Supply Chain Innovation; Community-Based Economy; Regional Planning